2016
DOI: 10.1002/phar.1682
|View full text |Cite
|
Sign up to set email alerts
|

Lack of an Effect of Ritonavir Alone and Lopinavir-Ritonavir on the Pharmacokinetics of Fenofibric Acid in Healthy Volunteers

Abstract: Study Objective As we previously observed a significant 41% reduction in gemfibrozil exposure after 2 weeks of lopinavir-ritonavir administration, we sought to determine the influence of lopinavir-ritonavir and ritonavir alone on the pharmacokinetics of fenofibric acid, an alternative to gemfibrozil for the treatment of elevated triglyceride levels. Design Open-label, single-sequence pharmacokinetic study. Setting Clinical Research Center at the National Institutes of Health. Subjects Thirteen healthy ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…RPECs were viable across all concentrations of fenofibrate used in the cytotoxicity experiments ( Figure ). Concentrations of fenofibrate 1–50 μM were used in the experimental treatment groups as they represent expected plasma concentrations across the clinical spectrum (i.e., the range of fenofibrate's peak plasma concentration C max in plasma is between 26 and 30 μM) …”
Section: Resultsmentioning
confidence: 99%
“…RPECs were viable across all concentrations of fenofibrate used in the cytotoxicity experiments ( Figure ). Concentrations of fenofibrate 1–50 μM were used in the experimental treatment groups as they represent expected plasma concentrations across the clinical spectrum (i.e., the range of fenofibrate's peak plasma concentration C max in plasma is between 26 and 30 μM) …”
Section: Resultsmentioning
confidence: 99%
“…Compared with baseline, RTV decreased fenofibrate AUC by 11% (p > 0.05) and C max was unchanged, and L/R decreased fenofibrate AUC by 13% (p > 0.05) and C max was unchanged. The authors concluded that fenofibrate can safely be given with either L/R or ritonavir alone [42]. The same authors reported a significant 41% reduction in gemfibrozil exposure after 2 weeks of L/R administration.…”
Section: Lopinavir/ritonavir + Lipid-lowering Therapiesmentioning
confidence: 92%
“…Aspirin, Prasugrel [20], Cangrelor, GPIIb/IIIa Clopidogrel [16,17] Ticagrelor [24][25][26], Vorapaxar Lipids lowering agents Pitavastatin [36,37], pravastatin, Fluvastatin, Ezetimibe, Fenofibrate [42], PCSK9inhibitors…”
Section: Antiplatelet Agentsmentioning
confidence: 99%
“…Fenofibric acid (90568-10MG, Sigma-Aldrich, St. Louis, MO, USA) was dissolved in DMSO and added to the incubation medium to achieve the indicated drug concentrations. The in vitro concentrations of fenofibric acid were determined from the Cmax plasma concentrations from previously reported patient samples [ 49 , 50 , 51 ]. Cells were treated for 24 h; the DMSO concentration used never exceeded 0.1% DMSO.…”
Section: Methodsmentioning
confidence: 99%